Percutaneous transcatheter arterial embolization in haemodynamically stable patients with blunt splenic injury - Popović, Peter (Radiology and oncology (Ljubljana), 2010)
Background. The nonoperative management of the blunt splenic injuryand the patient was treated with the selective distal splenic artery embolization withmicrospheres. Postprocedural insupraselective embolization with microspheres. haemodynamically stableultrasound and computed tomography follow-up a year later revealed only a small area of parenchymal irregularity. patients hasCase report. A young hockey player was brought to the Emergency Conclusions. The percutaneous splenic arterial embolization has a major role in the management of traumatic Department with the history of blunt abdominalsplenic injuries. Embolization is particularly beneficial in injuries of grade III or higher.
Keywords: embolizacija; poškodbe; therapy; trebušna votlina; vranica; zdravljenje